Методика проведення експеременту робочого процесу пневмотранспортера обчісаного вороху - Головльов, В. А.; Леженкін, Олександр Миколайович; Леженкин, Александр Николаевич; Lezhenkin, Oleksandr (ТДАТУ, 2020)
UK: У статті наводяться переваги збирання зернових колосових методом обчісування на корені з послідуючою доробкою на стаціонарів порівнянні з прямим комбайнуванням. Реалізація цієї технології стримується недостатньо обґрунтованістю пневмотранспортеру обчісаного вороху. У зв’язку з цим виникає проблема дослідження пневмотранспортеру, за для її рішення була розроблена методика експериментальних досліджень, яка дозволить визначення оптимальних параметрів і показників роботи пневмотранспортеру обчісаного вороху. Було обрано повно факторний дослід із кількістю дослідів рівній 27 за планом Бокса–Бенкіна. Критеріями оцінки функціонування були обрані дальність польоту та питома енергоємність. Факторами обрані: частота обертання валу відцентрового вентилятору, питома подача вихідного матеріалу, кут нахилу рухомої заслінки. Використовуючи результати теоретичних досліджень, моделювання та аналізу літературних джерел були визначені границі значень факторів. Для загальної картини наведена схема лабораторної установки з описом й поясненням принципу роботи. RU: В статье приводится преимущества уборки зерновых колосовых методом очеса на корню с последующей доработкой в сравнении с комбайнированием. Реализация этой технологии сдерживается недостаточно обоснованностью пневмотранспортера очесанного вороха в связи с чем возникает проблема исследования, ради ее решения была разработана методика экспериментальных исследований, которая позволит определить оптимальные параметры и показателей работы. Был выбран полно факторный опыт с количеством опытов равным 27 по плану Бокса-Бенкина. Критериями оценки функционирования были выбраны: дальность полета и удельная энергоемкость; а факторами: частота вращения вала, удельный подача исходного материала, угол наклона подвижной заслонки. EN: The article presents the advantages of harvesting grain ears by the method of combing at the root use stripper harvesting module technology with subsequent processing in comparison with combining. The implementation of this technology is constrained by namely the lack of scientific substantiation of the operating modes of the pneumatic conveyor of the combed heap. In this regard, there is a problem of researching the pneumatic conveyor, for its solution a method of experimental research was developed, which will determine the optimal parameters and performance of the pneumatic conveyor combed heap. A full-factor experiment was chosen with the number of experiments equal to 27 according to the Box – Benkin plan. Criteria for assessing performance were selected flightrange and specific energy consumption. Factors selected: the speed of the centrifugal fan shaft, the specific feed of the source material, the angle of the movable damper. Using the results of theoretical research, modeling and analysis of literature sources, the limits of factor values were determined. For the general picture the scheme of laboratory installation with the description and explanation of the principle of work is resulted. The working process of the experimental installation is as follows: the combed heap is fed from the scraper conveyor to the channel of the pneumatic conveyor, where the air flow forced by the centrifugal fan picks up the combed heap and feeds it to the exit where the trajectory is regulated by a movable flap.
Методика проведения эксперимента рабочего процесса пневмотранспортера очесанного вороха
Method of conducting the experiment of the working process of the pneumatic conveyor of the combed heap
Keywords: обчісаний ворох; методика; експеримент; дослідження; критерії оцінки; фактори; эксперимент; очесаный ворох; исследование; критерии оценки; факторы; combed heap; technique; experiment; research; assessment criteria; factors